Enarodustat suppresses thymic stromal lymphopoietin expression via hypoxia-inducible factor-mediated c-Jun N-terminal kinases dephosphorylation - Ryosuke Segawa; Makiko Yagisawa; Chihiro Miyata; Noriyasu Hirasawa (PLoS ONE, 2026)
Thymic stromal lymphopoietin (TSLP) is an epithelial-derived cytokine that induces type 2 immune responses through dendritic cell activation, and its aberrant regulation is implicated in TSLP-associated inflammatory disorders including atopic dermatitis. We previously demonstrated that hypoxia-inducible factor (HIF) suppresses TSLP expression in human keratinocyte cells; however, the underlying mechanism remained unclear. In this study, we aimed to explore the suppressive mechanism of enarodustat, an HIF-prolyl hydroxylase inhibitor. Enarodustat selectively suppressed TSLP expression induced by the fibroblast-stimulating lipopeptide (FSL-1), a toll like receptor 2/6 agonist in HaCaT, a human keratinocyte cell line. Although both the nuclear factor-κB (NF-κB) and activator protein (AP)-1 contributed to FSL-1-induced TSLP induction, enarodustat preferentially attenuated AP-1 signaling by reducing c-Jun N-terminal kinase (JNK) phosphorylation. This JNK dephosphorylation required both HIF1α and HIF2α and was accompanied by increased expression of dual-specificity phosphatases (DUSPs), which target JNK for dephosphorylation. Collectively, our findings identify a previously uncharacterized HIF–DUSP–JNK axis that negatively regulates TSLP expression. This study provides mechanistic insight into how HIF activation shapes epithelial cytokine responses, offering a basis for understanding the pathogenesis of TSLP-associated diseases such as atopic dermatitis.